The Two-Stage Air-CO Activation in the Preparation of Activated Carbons. II. Characterization by Adsorption from Solution - A. Linares-Solano; F. Rodríguez-Reinoso; M. Molina-Sabio; J. de D. López-González (Adsorption Science & Technology, 1984)
Olive stones and almond shells have been used as raw materials to prepare activated carbons following three different experimental methods: (a) carbonization in N 2 followed by activation in CO 2 , (b) direct activation in CO 2 and (c) treatment in dry air at 573 K followed by activation in CO 2 . The carbons have been characterized by the adsorption of paranitrophenol, methylene blue, orange II, crystal violet and victoria blue, all in aqueous solution. Methods (a) and (b) yield carbons with very similar adsorptive capacities and carbons prepared by method (c) have larger adsorptive capacities for similar overall yields. On the other hand, carbons from almond shells (more microporous) would be more suitable for adsorption of small solutes and carbons from olive stones (more macroporous and consequently, with larger rate of adsorption) for larger dimension molecules.